Customers' intention to visit fast food restaurants in Malaysia: a lesson learned from Covid-19 pandemic - Ghazali, Hazrina; Zamzuri Anuar, Zarisha Azwa; Ismail, Nurul Ashikin (Human Resource Management Academic Research Society, 2022)
COVID-19 has flipped billions of people's lives upside down worldwide, and its consequences extend beyond physical health, affecting society and economics. The outbreak of this disease has severely affected the global and Malaysian economy. Among the economic sectors which are suffering loss, the service industry particularly, fast food restaurants, are hugely impacted. Before the outbreak of COVID-19, most consumers enjoyed going out and dine-in at a fast-food restaurant without feeling paranoid. The purpose of this study is to examine factors that influence consumers' intention to visit fast-food restaurants during COVID-19 pandemic. In this study, three independent variables were used: consumers' perceived risk, sales and promotion, and service quality. Online questionnaires were used as medium of data collection to customers of fast-food restaurants and after data screening, a total of 240 questionnaires were valid for further analysis. Data obtained was analyzed by using SPSS's latest version. The results of service quality (mean=3.76), sales promotion (mean=3.59) and perceived risk (mean=3.54) indicate a score leaning towards agreement level. Results showed that sales promotion (beta value: 0.256, sig-t: 0.000) is the most influential factor of consumers’ intention to visit a fast-food restaurant and followed by the perceived risk and service quality. Additionally, findings obtained from this study found that perceived risk, sales promotion and service quality have a significant relationship with intention to visit fast food restaurants during COVID-19 pandemic. It is expected that this study will help to assist the fast-food restaurant operators to focus on these three factors to take the necessary action to seek consumers' satisfaction and make them feel secure to dine in during this COVID-19 pandemic.